Does agglomeration boost innovation? An econometric evaluation - Megha Mukim (European Regional Science Association (ERSA), 2010)
Innovation is crucial to regional economic competitiveness and to productivity growth. A salient feature of the Indian economy is the geographic concentration of both, economic activity and innovation, as measured by patent activity. Theoretical models argue that the clustering of economic activity within a geographic region results in knowledge spillovers, which in turn drives innovation. The literature also posits that the presence of human capital is critical to the generation of new knowledge. This paper studies how and why economic geography and factor endowments matter for innovative activity - in other words, what is the relationship between human capital and patent generation, and crucially, how is this affected by the spatial distribution of economic activity? The paper analyses patent activity, both applications and grants, between 1995 and 2004 across districts in India. By using an econometric model, it then relates innovation to measures of agglomeration, industry-type and the size distribution of firms, and to the distribution of human capital endowments. It also uses data on employment by industrial activity, productivity and FDI flows. Understanding the magnitude of the effects of economic geography and factor endowments is vital for policy formulation aimed at encouraging innovative activity.
Keywords: R12; O3; 330